Pengaruh Work Life Balance, Burnout Dan Lingkungan Kerja Terhadap Kepuasan Kerja (Studi Pada Karyawan BPKAD Kota Metro) - Falentiyo, Rian; Nasikah, Durotun (Universitas Muhammadiyah Metro, 2022)
Based on field findings, it was found that the problems often experienced by employees at the Metro City BPKAD Office during the recent pandemic were work pressure increased when the pandemic situation worsened, this made it difficult for many employees to divide work time both at work and at home. The purpose of this study was to determine the effect of Work Life Balance, Burnout and Work Environment on Job Satisfaction in Metro City BPKAD employees.This research is quantitative research. With this type of explanatory survey research. The sampling technique is a saturated sample technique with the determination of the sample used as a whole from a population of 56 employees. As a measuring tool used 80 questionnaire items with Likert scale measurements and analyzed using multiple linear regression. Methods of data collection by observation, interviews, questionnaires and documentation.The results of the study using the t-test (partial) showed a positive value of the effect of work life balance on job satisfaction, namely tcount> ttable (1,724>1,675), the negative value of the effect of burnout on job satisfaction was tcount> ttable (1,447<1,675), and a positive value from the work environment to job satisfaction that is tcount> ttable (1,966>1,675). While the f (simultaneous) test shows the value of the effect of work life balance, burnout, work environment simultaneously on job satisfaction, namely fcount > ftable (27.662 > 2.56). From the calculation of the value of R square, the ability of the independent variable in explaining the variance of the dependent variable is 61.5%, which means that there is 38.5% of the variance of the dependent variable explained by other factors not examined.